Семантичний потенціал прикметників англійської мови - Чаварга, Я. (Лексикографічний бюлетень, 2006)
The article deals with the exponential dependence of the quantity of polysemantic adjectives in Modern English on the quantity of their meanings. The concrete form of this exponent is found and its linguistic interpretation is given. Three semantic potentials of English polysemantic adjectives are distinguished on the basis of our investigations: the usual, the increased and the high potential of creating new meanings.